ChemInform Abstract: Modular Access to Highly Functionalized Tetrahydroquinolines. Issue 16 (April 2015) - Cordero, Franca M.; Khairnar, Bhushan B.; Brandi, Alberto
Abstract 1, 3‐Dipolar cycloaddition of o‐bromostyrene (II) or analogues (X) to nitrones produces mixtures of isoxazolidine structures.